2007
DOI: 10.1289/ehp.10009
|View full text |Cite
|
Sign up to set email alerts
|

Half-Life of Serum Elimination of Perfluorooctanesulfonate,Perfluorohexanesulfonate, and Perfluorooctanoate in Retired Fluorochemical Production Workers

Abstract: BackgroundThe presence of perfluorooctanesulfonate (PFOS), perfluorohexanesulfonate (PFHS), and perfluorooctanoate (PFOA) has been reported in humans and wildlife. Pharmacokinetic differences have been observed in laboratory animals.ObjectiveThe purpose of this observational study was to estimate the elimination half-life of PFOS, PFHS, and PFOA from human serum.MethodsTwenty-six (24 male, 2 female) retired fluorochemical production workers, with no additional occupational exposure, had periodic blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
1,123
9
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,705 publications
(1,214 citation statements)
references
References 21 publications
44
1,123
9
11
Order By: Relevance
“…(1), provided that the covariates have constant multiplicative effects on serum concentrations over time. 7 Studies of post-shift workers, 2,5 retired workers, 4 fasting subjects, 6 and subjects undergoing exposure interventions 7,9 have used regression of log biomarker concentrations on time to estimate elimination rate constants and corresponding half-lives for environmental contaminants. However, Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1), provided that the covariates have constant multiplicative effects on serum concentrations over time. 7 Studies of post-shift workers, 2,5 retired workers, 4 fasting subjects, 6 and subjects undergoing exposure interventions 7,9 have used regression of log biomarker concentrations on time to estimate elimination rate constants and corresponding half-lives for environmental contaminants. However, Eq.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study of a retired US occupational cohort reported an average PFOA half-life estimate of 3.8 years from 5 years of follow-up with a baseline median serum PFOA concentration of 408 ng/ml and up to eight measurements per participant. 4 All three PFOA half-life estimates relied on some form of log concentration regression. By how much might these PFOA half-life study estimates be overestimated because of background exposures?…”
mentioning
confidence: 99%
“…For both genders of cynomolgus monkeys, an elimination half-life of about 20-30 days was found following dosing with PFOA , while a half-life of approximately 100-200 days was determined after exposure to PFOS (Seacat et al 2002). Based on recent monitoring of retired production workers, it has been demonstrated that both these perfluorochemicals have a relatively longer serum elimination half-life in humans (4.4 ± 3.6 years for PFOA vs. 8-9 years for PFOS) than in most mammals (Burris et al 2002;Olsen et al 2007). …”
Section: Comparison Of Elimination Of Pfoa Versus Pfos In Ratsmentioning
confidence: 99%
“…Besides, the negligible renal clearance of PFCs leads to a possibility of long-term exposure in human. For example, as one of the most concerned PFCs, PFOS is present in the blood of general population at a level of about 20 ppb and an estimated half-life of nearly 5.4 years (Calafat et al 2007;Olsen et al 2007). Because of the characteristics of wide distribution and high stability, there has been a great concern as to PFCs' potential harmful effects on human health (Steenland et al 2010).…”
Section: Introductionmentioning
confidence: 99%